Quality of Services and Facilities to Satisfaction (Satisfaction Of Facilities) D3 Accounting Alumni Through Importance Performance Analysis (IPA) Approach - Safier Ramdani; Adam Anugrah Pratama; Bagas Rizky Haryansyah (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
This research aims to provide information level of satisfaction D3 Accounting Uhamka alumni, surveyed at the graduation ceremony in December 2020. This research uses a descriptive quantitative approach with survey techniques. The population in this study were alumni of the D3 Accounting Uhamka who graduated in December 2020. Data collection method for this study used survey techniques. Main instrument used for this research is a questionnaire that is distributed to the respondents. The questionnaire consists of assessing the level of alumni satisfaction with the services provided by the D3 Accounting Uhamka. Data traced in this study are directly related to alumni satisfaction with the services provided by all service departments at D3 Accounting Uhamka. The results of the study show that the D3 Accounting Alumni response to the 2020/2021 University Leaders, 2020 FEB leaders, 2020/2021 FEB Study Program leaders, FEB D3 Accounting lecturers 2020/2021, FEB education staff 2020/2021, Infrastructure, personal impact All of which have been obtained from Education at UHAMKA have achieved satisfactory results.